Aspectos inflamatórios envolvidos na fibrilação atrial em uma população em uso de anticoagulantes orais - Gabriela Lopes Martins (2018)
Atrial fibrillation (AF) is the most common arrhythmia in clinical practice, and is associated with a high risk of stroke and systemic embolism. However, the pathophysiology of the disease has not yet been well elucidated. Evidence suggests that inflammation may play a role in the pathogenesis of AF and its maintenance, as well as in thrombosis related to this condition. Based on this, the present study had as objective to evaluate inflammatory parameters and markers related to cardiovascular diseases in individuals with atrial fibrillation (n = 71), in treatment with two oral anticoagulants, warfarin (n = 42) or rivaroxaban (n = 29), as well as in one group of control subjects (n = 52), for comparison. For this purpose, in plasma samples of individuals with mean age of 70 years, the quantification of inflammatory mediators and markers related to cardiovascular diseases by Cytometric Bead Array (CBA) and LUMINEX®, respectively, were performed. The results showed that subjects with atrial fibrillation, compared to controls, presented significantly elevated values of various inflammatory parameters, including mediators whose association with AF had not been described in previous studies, such as IL-4, IFN-γ and IP-10. Regarding the dosage of markers related to cardiovascular diseases, subjects with AF presented significantly elevated levels of GDF-15 and lipocalin-2/NGAL in relation to controls. Furthermore, when comparing subjects with AF in relation to anticoagulants, in general, higher levels of inflammatory parameters such as IL-2, IL-4 and IL-10 were observed in those taking warfarin compared to rivaroxaban. In view of the above, it was possible to relate inflammation to atrial fibrillation and to identify potential markers for predicting the occurrence and progression of the disease, as well as to verify a possible anti-inflammatory effect of rivaroxaban. In summary, this study showed that an understanding of the mechanism of inflammation in the pathophysiology of AF can provide opportunities for innovation in the prevention, therapy and management of patients with this arrhythmia.